Pressure independent index for arterial pulse waveform - Ho, Clement Wei En. (2012)
Knowing that arteries stiffen with age, this project involves the study of arterial pulse waveform for the nomotension population of different age groups. The aim is to establish the best possible parametric representation with respect to age.